2001
DOI: 10.1021/om0105066
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Rigid Ferrocene-Based Macrocycle from High-Resolution X-ray Powder Diffraction

Abstract: A macrocycle, 6, has been synthesized in high yield from 2,5-di(pyrazol-1-yl)hydroquinone and 1,1′-fc[B(Me)NMe 2 ] 2 {fc ) Fe(C 5 H 4 ) 2 }. The molecule incorporates two redox-active 1,1′ferrocenylene units in its backbone and contains four chiral boron centers, each of them possessing the same configuration. It is demonstrated that crystal structures of organometallics of moderate complexity can be solved from high-resolution X-ray powder diffraction patterns, once the connectivity between the functional gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…DFT lattice-energy minimizations are becoming available for increasingly large unit cells. In a recent study of C 24 H 22 B 2 N 4 O 2 Fe using synchrotron radiation (Dinnebier et al, 2002), 220 atomic positions in a volume of 2076 A Ê 3 were optimized, resulting in excellent agreement with the experimental data after Rietveld re®nement with ®xed atomic coordinates.…”
Section: Dft Calculations Versus Experimental Datamentioning
confidence: 75%
“…DFT lattice-energy minimizations are becoming available for increasingly large unit cells. In a recent study of C 24 H 22 B 2 N 4 O 2 Fe using synchrotron radiation (Dinnebier et al, 2002), 220 atomic positions in a volume of 2076 A Ê 3 were optimized, resulting in excellent agreement with the experimental data after Rietveld re®nement with ®xed atomic coordinates.…”
Section: Dft Calculations Versus Experimental Datamentioning
confidence: 75%
“…Furthermore, reactions of equimolar amounts of qpy with a disubstituted ferrocene precursor yielded a mixture of macrocyclic stereoisomers, 33 a and 33 b . Although, X‐ray quality crystals were elusive, analyses of related structures present suitable evidence to suggest that isomer 33 a is the more favorable 46. The 11 B NMR spectrum of 33 exhibited a broad signal at δ =12.4 ppm characteristic of tetracoordinate boronium center while ESI‐MS of 33 yielded two prominent peaks at m / z 691 and 412 corresponding to [ 33 ‐(PF 6 ) 2 ] 2+ and [ 33 ‐PF 6 ] 3+ , respectively.…”
Section: Syntheses and Structures Of Borocationsmentioning
confidence: 99%
“…There is no steric hindrance to synthesise 1,1'-bis(N,N'-dimethyl-1,3,2-diazaborolidyl)-ferrocene (16). This compound was first described by Herberhold et al [27].…”
Section: Organylaminoborylferrocenesmentioning
confidence: 99%
“…Meanwhile, a large number of monoborylated and 1,1'-diborylated ferrocenes are known as well as tri-and tetraborylated ferrocenes [13][14][15][16][17][18][19][20][21]. Siebert et al [13], Wrackmeyer et al [14. 18] and we [2,20] have shown that the reaction of ferrocene, ruthenocence and osmocene with BBr 3, depending on the stoichiometry, produces the dibromoboryl metallocenes (Br 2 BCp)MCp, (Br 2 BCp) 2 Meanwhile it is well known that this bending depends strongly on the Lewis acidity of the boryl BX 2 substituent [19,21].…”
Section: Introductionmentioning
confidence: 99%